Factors Associated With Participation Rate and Predictive of Improvement After Cardiac Rehabilitation in Patients With Heart Failure. Issue 1 (14th January 2023) - Wu, Li-Hua; Wang, Chao-Hung; Liu, Min-Hui; Hsu, Chih-Chin; Yuan, Pei-Hsun; Fu, Tieh-Cheng
Abstract : Patients with heart failure (HF) are often limited in their ability to perform exercise. Cardiac rehabilitation (CR), recommended for stable HF patients, improves cardiorespiratory fitness; however, it is underutilized. This study explored the factors associated with CR participation and completion rates from a single center and predictive of improvement after CR. Abstract : Purpose: Patients with heart failure (HF) are often limited in their ability to perform exercise. Cardiac rehabilitation (CR) improves aerobic capacity and quality of life (QOL) and is recommended for patients with clinically stable HF; however, it is underutilized. The aim of this study was to investigate the factors associated with participation and completion rates and predictive of improvement after phase II CR in patients with HF. Methods: Participation and completion rates were calculated for all patients with HF enrolled in a multidisciplinary management program from October 2008 to December 2018. Functional capacity and QOL were estimated. In patients undergoing CR, changes in peak oxygen uptake (V˙o 2peak ) were measured. Results: Of 662 patients enrolled, 448 (68%) completed the cardiopulmonary exercise test (CPX). Phase II CR was recommended in 411 patients, of whom 291 (71%) participated in CR. Participation was significantly related to sex and the time interval in days between hospital discharge and the CPX. Overall, 171 patients completed 36 sessions of CR (with a completion rate of 59%). During CR, there were 18 (6%) adverse events. Cardiac rehabilitation was associated with improvement in V˙o 2peak from 1153 ± 393 to 1342 ± 470 mL/min (a 16% improvement; P < .001) and in QOL. The independent predictors of increase in V˙o 2peak included sex, age, diabetes mellitus, and entry V˙o 2peak . Conclusions: In patients with HF, factors associated with CR participation rate included sex and days between hospital discharge and the CPX. Participation in CR improved V˙o 2peak and QOL. The improvement was related to male sex, younger age, no diabetes mellitus, and higher entry V˙o 2peak .